Autonomy in the face of a devastating diagnosis. Issue 2 (April 1998) - Spriggs, M
Abstract : Literary accounts of traumatic events can be more informative and insightful than personal testimonials. In particular, reference to works of literature can give us a more vivid sense of what it is like to receive a devastating diagnosis. In turn this can lead us to question some common assumptions about the nature of autonomy, particularly for patients in these circumstances. The literature of concentration camp and labour camp experiences can help us understand what it is like to have one's life-plans altered utterly and unexpectedly. Contrary to common views of autonomy which have difficulty in characterising autonomous action when long-standing assumptions are suddenly lost, these examples show that autonomy is possible in these circumstances. We need a theory of autonomy which can deal with traumatic events and is useful in the clinical context.